Mozaic of Phylosophy and Physicis in Tourism with View to Climate - Ana Njegovanović (Financial Markets, Institutions and Risks)
Tourism is attracting increasing attention of various scientific disciplines with the aim of studying phenomena in tourism from a specific disciplinary point of view. On issues in the field of philosophy and tourism, we find a large gap because, unlike many and diverse other scientific studies, a philosophical approach to tourism is practically non-existent. In understanding the complex concept of space and time, we need a basic knowledge of physics and neuroscience. Space and time in neuroscience remain separate coordinates to which we attach our observations. Spatial-temporal sequences of brain activity often correlate with measures of distance and duration, and these correlations may not correspond to neural representations of space or time. MIT neuroscientists have identified a brain circuit in the hippocampus that encodes the time of the event, that is, pyramidal cells (green) have been discovered in the CA2 region of the hippocampus that are responsible for storing critical time information. When we experience a new event, our brain records the memory not only of what happened, but also of the context, including the time and place of the event.